Legal Enforceability of Forum Selection Clauses in Preliminary Sale and Purchase Agreements for Cross-Regional Transactions - Timotius Febry Cristian Wahyu Sutrisno; Trinas Dewi Hariyana; Ali Huristak Hartawan Hasibuan; Zico Junius Fernando (The Indonesian Journal of International Clinical Legal Education, 2026)
The increasing use of Preliminary Sale and Purchase Agreements (Perjanjian Pengikatan Jual Beli/PPJB) in cross-regional land transactions has generated legal uncertainty regarding the enforceability of forum selection clauses, particularly where the parties, the designated forum, and the immovable property are located in different judicial jurisdictions. This study aims to examine the legal basis for the validity of forum selection clauses under Article 118 of the Herziene Indonesisch Reglement (HIR) and Article 1338 of the Indonesian Civil Code, as well as their implications for the relative jurisdiction of district courts and the delegated execution of judgments. The study employs normative legal research using statutory, conceptual, and case approaches through qualitative analysis of legislation, legal doctrines, and Supreme Court jurisprudence. Unlike previous studies that discuss forum selection clauses in isolation, this research develops an integrated analytical framework by linking the legal character of PPJB, contractual autonomy, relative jurisdiction, Supreme Court jurisprudence, and delegated execution involving immovable property. The findings demonstrate that a forum selection clause incorporated into a valid PPJB constitutes a binding manifestation of the principle of freedom of contract and is enforceable under Article 118(4) HIR in conjunction with Article 1338 of the Civil Code. Nevertheless, such contractual autonomy applies only to the adjudication stage and does not override the territorial principle governing the execution of judgments under Article 195 HIR. Accordingly, judgments rendered by the designated court remain enforceable through delegated execution by the district court where the immovable property is located. This study contributes to the harmonization of Indonesian contract law and civil procedural law while providing practical guidance for judges, notaries, and legal practitioners in resolving disputes arising from cross-regional PPJB transactions.